Diabetes and kidney cancer risk among post-menopausal women: The Iowa women’s health study - Wang, Shuo (Maturitas, 2020)
BACKGROUND: Many studies have reported a positive association between diabetes and kidney cancer. However, it is unclear whether diabetes is a risk factor for kidney cancer independent of other risk factors, such as obesity and hypertension. We comprehensively examined the association of diabetes and its duration with incident kidney cancer in the prospective cohort Iowa Women’s Health Study (1986–2011). METHODS: Diabetes status was self-reported at baseline (1986) and on five follow-up questionnaires. Cox proportional hazards regression was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations of baseline and time-dependent diabetes with the risk of incident kidney cancer. RESULTS: During the 25 years of follow-up, 245 cases of kidney cancer occurred among 36,975 post-menopausal women. In an age-adjusted model, there was a significant association between time-dependent diabetes and the risk of kidney cancer [HR (95% CI) = 1.76 (1.26, 1.45)]; the association was attenuated after multivariable adjustment for age, body mass index (BMI), waist-to-hip ratio (WHR), hypertension, physical activity, diuretic use, pack-years of smoking, alcohol intake, and total caloric intake [HR = 1.35 (0.94, 1.94)]. However, among non-obese women or women with a waist circumference less than 34.6 in., diabetes was significantly associated with kidney cancer risk: for time-dependent diabetes, HRs (95% CIs) were 1.82 (1.10, 3.00) among those with BMI < 30 kg/m(2) and 2.18 (1.08, 4.38) among those with a waist circumference < 34.6 in.. CONCLUSIONS: Our results suggest that diabetes is associated with kidney cancer risk among non-obese post-menopausal women.